Palliative care in Australian medical student education. (January 2014) - Cheng, Daryl R.; Teh, Andrew
<x xml:space="preserve">Abstract</x> Greater emphasis needs to be placed on medical student palliative care education within the Australian arena. The development of a comprehensive, relevant and practical educational curriculum in this area during medical school is imperative in order to adequately equip the future junior medical workforce. Further development of a national palliative care curriculum as well as research comparing various teaching methods and curricula should be the priorities in the near future.